Comparative Analysis of Zinc Levels in Patients with Chronic Leg Ulcers and Healthy Individuals: A Cross-Sectional Study - Sajad Ahmad, Afzal Khan, Sadia Dilawer, Akhtar Zaman, Tahir Angez Khan, Javed Iqbal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Zinc is an essential trace element critical to immune function and wound healing. Chronic leg ulcers are persistent wounds that affect millions of individuals globally. Zinc deficiency has been implicated in the pathophysiology of wound healing, but its role in chronic leg ulcers remains underexplored. Objective: To compare the serum zinc levels in patients with chronic leg ulcers to those of healthy individuals. Methodology: A cross-sectional study was conducted with 110 participants, divided into two groups: 55 patients with chronic leg ulcers and 55 age- and sex-matched healthy individuals. Serum zinc levels were measured using atomic absorption spectrometry. Statistical analysis was performed using the t-test (for normally distributed data) or Mann-Whitney U test (for non-normally distributed data). Results: The mean zinc level in the chronic leg ulcer group was significantly lower than the healthy control group (p < 0.05). The results also showed a negative correlation between zinc levels and the severity of the ulcers. Conclusion: Chronic leg ulcer patients have significantly lower zinc levels compared to healthy individuals, suggesting a potential link between zinc deficiency and impaired wound healing in such patients. Keywords: Zinc, chronic leg ulcers, wound healing, serum zinc levels, deficiency, cross-sectional study.